Investigate the effectiveness, mechanisms, and scalability of community-based interventions designed to reduce health disparities - Partiwi, Nur (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study investigates the effectiveness, mechanisms, and scalability of community-based interventions designed to reduce health disparities in urban populations. Research Design and Methodology: A mixed-methods approach was employed, integrating quantitative data from structured surveys and health measurements with qualitative data from in-depth interviews and focus groups. The sample consisted of 300 urban residents, primarily from low-income neighborhoods, and community health workers (CHWs). Findings and Discussion: The findings demonstrate that community-based interventions have a significant impact on improving health outcomes, including better management of chronic diseases, healthier eating habits, and enhanced mental well-being. Community engagement, empowerment, and the utilization of local resources emerged as critical in driving these positive outcomes. The study supports the social determinants of health theory and aligns with previous research while providing new insights into the mechanisms of successful interventions. Stable funding, policy support, and adaptable models were identified as crucial for the scalability and sustainability of these interventions. Implications: The study highlights the importance of integrating Community Health Workers (CHWs) into urban healthcare strategies, expanding community-led nutrition and mental health programs, and securing stable funding and policy support. Despite limitations such as sample size and reliance on self-reported data, the research provides valuable guidance for policymakers and healthcare providers to develop more equitable and effective healthcare systems. Future research should focus on larger, more diverse samples and integrate health technologies to enhance the effectiveness and scalability of interventions.